Criteria for assessing the severity of infectious mononucleosis in children - O. A. Popova; Z. A. Khokhlova (LLC "Diagnostics and Vaccines", 2019)
This article will discuss the criteria for assessing the severity of the complication of infectious mononucleosis at children. The method for determining the degree of severity of the disease using a point - based assessment for each clinical symptom and the results of standard laboratory studies is proposed. The method allows on the day of treatment to clarify the severity of infectious mononucleosis and choose the tactics of patient management.